SPECTROPHOTOMETRIC STANDARDS 8m-10m. II.THE EQUATORIAL ZONA FROM 0h TO 12h. - Tereschenko, V.M. (Academic Scientific Journal of Computer Science, 2020)
This article is the second paper from cycle of notices, which devoted of the creation of spectrophotometric standards of intermediate brightness. In paper the absolute energy distribution in visual region of spectra for 12 B-A-stars 8m-10m were present. The standards such brightness is necessary first of all for calibration of the spectral observations on the big telescopes. The investigated stars-standards are located along the celestial equator in the range of right ascensions from 0h to 12h. Observations were made on the telescopes of AZT-8 and Zeiss-600 with the help of a diffraction spectrograph with toroidal grating. The receiver of radiation was served CCD-camera ATIC 490EX. Equipment, observation methods, reductions and computations detailed described in our first paper. The distribution of energy was studied in the range of 345нм - 665nm, the spectral resolution of the data is 5nm, the relative standard error of the received data - from 2 to 6%. The reliability of the results is assessed by comparing the calculated and directly observed star magnitudes of the investigated stars in the UBV-system.